2013
DOI: 10.1186/1756-8722-6-45
|View full text |Cite
|
Sign up to set email alerts
|

Early stage follicular lymphoma: what is the clinical impact of the first-line treatment strategy?

Abstract: BackgroundLess than 20% of patients with follicular lymphoma (FL) present with Ann Arbor Stage I or II disease at diagnosis. Numerous therapeutic options exist, however radiation therapy is considered the standard of care for early-stage disease based on single-institution or retrospective series. Our aim was to revisit the outcome of patients with localized FL in the rituximab era.Patients and MethodsWe analyzed the characteristics and outcomes of 145 early-stage FL patients, who were retrospectively divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Another recent retrospective study divided patients into 6 groups according to their initial treatment: observation, RT alone, chemotherapy, RT with chemotherapy, rituximab monotherapy, and chemoimmunotherapy. 26 Similar to the findings of the LymphoCare database analysis, OS did not differ between treatments at 7.5 years, whereas PFS at 7.5 years was significantly higher with chemoimmunotherapy versus all other treatments (P ¼ .00135). 26 Accordingly, although these studies challenge the use of RT alone as the standard of care for localized FL, they are limited by their retrospective design and small numbers of patients.…”
Section: Radiotherapysupporting
confidence: 76%
See 2 more Smart Citations
“…Another recent retrospective study divided patients into 6 groups according to their initial treatment: observation, RT alone, chemotherapy, RT with chemotherapy, rituximab monotherapy, and chemoimmunotherapy. 26 Similar to the findings of the LymphoCare database analysis, OS did not differ between treatments at 7.5 years, whereas PFS at 7.5 years was significantly higher with chemoimmunotherapy versus all other treatments (P ¼ .00135). 26 Accordingly, although these studies challenge the use of RT alone as the standard of care for localized FL, they are limited by their retrospective design and small numbers of patients.…”
Section: Radiotherapysupporting
confidence: 76%
“…[25][26][27][28][29][30][31][32][33][34][35] In identified studies, the median age of patients with localized FL generally ranged from 50 to 64 years. Although a few studies reported that age was an independent prognostic factor for outcome, with younger age being NG CR: 80.9% PR: 9.5% SD: 0% PD: 9.5% (All data for RT alone) Abbreviations: BCCA ¼ British Columbia Cancer Agency; BNLI ¼ British National Lymphoma Investigation; CLI ¼ central lymphatic irradiation; CR ¼ complete response/remission; CSS ¼ cause-specific survival; CT ¼ chemotherapy; DFS ¼ disease-free survival; DSS ¼ disease-specific survival; EFRT ¼ extended field radiotherapy; EFS ¼ event-free survival; FFLP ¼ freedom from local progression; FFP ¼ freedom from progression; FFTF ¼ freedom from treatment failure; FL ¼ follicular lymphoma; IFRT ¼ involved field radiotherapy; INRT ( 5 cm) ¼ involved node radiotherapy (with margins up to 5 cm); IRRT ¼ involved regional radiotherapy; NCRI ¼ National Cancer Research Institute; NG ¼ not given; NHL ¼ non-Hodgkin lymphoma; NS ¼ not significant; ORR ¼ overall response rate; OS ¼ overall survival; PD ¼ progressive disease; PFS ¼ progression-free survival; PR ¼ partial response/remission; RFS ¼ relapse-free survival; RR ¼ response rate; RT ¼ radiation therapy; SD ¼ stable disease; SEER ¼ Surveillance Epidemiology and End Results; STLI ¼ subtotal lymphoid irradiation; TBI ¼ total body irradiation; TLI ¼ total lymphoid irradiation; TNI ¼ total nodal irradiation.…”
Section: Radiotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the indolent clinical course, it is reasonable to assume that a fraction of such E. Mamessier et al 806 haematologica | 2014; 99(5) patients remain undiagnosed, potentially for many years. Based on trials showing no benefit of immediate chemotherapy in patients with a low tumor burden, 73,74 current guidelines recommend a WW approach, deferring treatment initiation until worsening of disease and/or clinical symptoms appear. 75 Most patients with a low tumor burden under WW have an improved quality of life for an average period of 2.5 years by delaying exposure to the toxic side-effects of chemotherapy, the reduced number of hospital visits and related interventions (therapeutic agents administration, blood puncture, etc.).…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…5,6 Moreover, irradiation is the only treatment strategy to demonstrate any advantage in terms of overall survival, although the evidence for this was obtained from retrospective studies. 7,8 However, the reality is that several treatment strategies have been applied for patients with early-stage FL, including combined-modality therapy (CMT), irradiation alone, watch-and-wait (WW), and more recently, rituximab (R)-containing chemotherapy or R monotherapy, [9][10][11] probably because recommendations have been based on relatively small, retrospective studies from a single center. 5,6 Diseasefree survival rates for patients with early-stage disease were Clinical management and outcomes of completely resected stage I follicular lymphoma Norifumi Tsukamoto 9) 44 -54% at 10 years when treated with involved-field irradiation.…”
Section: Introductionmentioning
confidence: 99%